The portrayal of Jews in modern Biełarusian literature - Gimpelevich, Zina J., 1949- (McGill-Queen's University Press, 2018)
"One of the notable distinctions of Biełarusian authors, compared to other writers in Slavic literatures, is their depiction of Jewish characters as natives to the land. The Jewish population in historic Biełarusian territories was the country's largest minority, and Yiddish was one of the state languages of Biełarus between 1919 and 1938. The Portrayal of Jews in Modern Biełarusian Literature sheds light on this little-known yet important part of Slavic and Jewish studies. Zina Gimpelevich demonstrates that the works produced by Biełarusian writers over a long period of time display a more consistent tolerance and sympathy towards Jews than has generally been recognized. Beginning several centuries ago but concentrating on the late nineteenth and twentieth centuries, she offers excerpts - and textual and comparative analyses - of works by Biełarusian poets, novelists, and dramatists, most of whom have not been previously translated into English. Each writer is discussed in terms of their socio-political background, and the country's history during the period in which they lived and wrote. Biełarusian literature influenced and enlightened public consciousness since the middle of the sixteenth century, despite the destructive actions of its many rulers. The Portrayal of Jews in Modern Biełarusian Literature offers deep insights into how the region's Biełarusian, Jewish, and other cultures interacted over many centuries."--